2018
DOI: 10.1111/iju.13698
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal women with recurrent urinary tract infections have lower quality of life

Abstract: Recurrent acute uncomplicated urinary tract infection has a negative impact on the quality of life of premenopausal, otherwise healthy women. Recurrent acute uncomplicated urinary tract infection patients who also have chronic constipation or consume caffeine have lower quality of life than those who do not. More studies are required to understand the relationships between these common problems and risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
2
25
0
2
Order By: Relevance
“…The study also showed that women with recurrent urinary infections have a compromise in physical and psychological aspects related to the quality of life, signi cantly higher than women in the control group. These results corroborate studies carried out with Asian and European women, with recurrent urinary tract infections, showing a wide negative impact of recurrent infections on the quality of life of women, mainly affecting the physical and mental dimensions [1,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study also showed that women with recurrent urinary infections have a compromise in physical and psychological aspects related to the quality of life, signi cantly higher than women in the control group. These results corroborate studies carried out with Asian and European women, with recurrent urinary tract infections, showing a wide negative impact of recurrent infections on the quality of life of women, mainly affecting the physical and mental dimensions [1,13].…”
Section: Discussionsupporting
confidence: 89%
“…Despite a recent multi-center European study pointing out that prophylactic treatment can reduce the number of infectious episodes and improve the quality of life of women, the lack of consensus on prophylaxis and treatment of recurrent urinary infections in Latin America hinders the adoption of prophylactic measures [1,2,13]. Thus, further studies are needed to assess the effectiveness, risks, and bene ts of different prophylactic options in the health and quality of life of women with recurrent urinary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) are among the most common urologic conditions in the older population . As the incidence of LUTS and frailty increases with age, the concept of frailty has been recognized as a key factor in older individuals with LUTS . However, only a few studies have evaluated the influence of frailty on LUTS .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) and their recurrence are associated with substantial health care burdens and morbidity globally, including impacts on the daily activities and quality of life of sufferers ( 1 , 2 ). UTIs are defined as either uncomplicated (uUTIs) or complicated (cUTIs).…”
Section: Introductionmentioning
confidence: 99%